Prézentní časování sloves vzorů »kryje« a »kupuje« ve spisovné češtině: variantnost, nebo unifikace? - Sojka, Pavel (Bohemistyka, 2021)
The morphological variation in the present-tense conjugation of the kryje and kupuje conjugation types (3rd verb class) as a result of gradual vowel shifts has been in progress since the 15th century. The gradual back shift towards the endings -u and -ou used to be explained as a result of paradigm levelling within the conjugation types of the 1st, 2nd and 3rd verb class. In 1993, these endings were codified alongside with the endings -i and -í. However, this codification act hasn’t met with general approval, because the incidence of the endings -u and -ou in standard language is not equal: while the ending -u has been standardizing, the ending -ou has still retained its markedness or can be even regarded as colloquial, in particular in written standard language. In this paper, we aim to answer the question how the endings -u and -ou are applied in present-day TV journalism, namely in the Interview ČT24 show.